Hubungan Antara Self-Esteem dengan Body Image pada Siswa Kelas XI di SMA Negeri 12 Bekasi - Siti Fatimah; Ari Sumitro; Amir Erwin (Guidance : Jurnal Bimbingan dan Konseling, 2020)
This study aims to find out the relationship between self-esteem and body image in grade XI students at SMA Negeri 12 Bekasi. This type of research uses descriptive analysis with correlational techniques. The number of subjects used in this study was 122 students of grade XI science and social sciences. Sampling techniques using simple random sampling. Data collection used is the psychological scale of self-esteem and body image questionnaires. After performing a validity test on the self-esteem scale obtained 29 valid items with very strong reliability (0.817), as well as the body image scale obtained 31 valid items with very strong reliability (0.907) and can be used as a data collection tool. The data analysis method used is the product-moment correlation test. The results showed the correlation coefficient r = 0.562 with the signification of p = 0.000 (p < 0.01) so that the conclusion of the results of this study showed that there is a significant relationship between self-esteem and body image in grade XI students at SMA Negeri 12 Bekasi.